Behavioral analyses of a forebrain glutamatergic neuron specific Ywhae conditional knockout mouse model - Meaghan Navarrete-Mathews; Gloria S. Lee; Angel Walerio; Dylan Horne; Yuying Wu; Yi Zhou (PLoS ONE, 2025)
The seven mammalian isoforms of 14-3-3 are each encoded by a unique gene and function as phosphorylation dependent protein modulators. Because 14-3-3 proteins have particularly high expression in the brain, they have been implicated in a variety of neuronal functions. Recently, we showed that functional knockout of all 14-3-3 isoforms in forebrain glutamatergic neurons of mice is sufficient to induce schizophrenia-like endophenotypes. Human and animal studies have linked mutations in Ywhae and 14-3-3ε expression changes to certain neurodevelopmental and psychiatric diseases. In this study, we conditionally knocked out 14-3-3ε from forebrain glutamatergic neurons by crossing Ywhae flox/flox mice with CaMKIIα-Cre mice. Ywhae flox/flox Cre + (conditional knockout -CKO) mice and their Ywhae flox/flox Cre - (double-flox control - dFlC) littermates were put through a battery of behavioral tests to assess their behavioral endophenotypes. Ywhae CKO mice exhibited significant differences from dFlC mice in some of the behaviors examined. We also found several significant sex differences within our model. Furthermore, we compared two viral 14-3-3 knockout methods and found that CaMKIIα promoter driven difopein expression in wildtype mice is more efficient than Cre/loxP driven difopein expression in CaMKIIα-Cre mice. Collectively our results indicate that knocking out 14-3-3ε in glutamatergic forebrain neurons via this strategy is not sufficient to induce schizophrenia-like behavioral alterations. In the future, using different mouse line or knockout scheme may help further elucidate the isoform specific role of 14-3-3ε in the forebrain.